1970
DOI: 10.1002/art.1780130105
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies of the passage of gold thiomalate across the renal glomerular capillary wall

Abstract: In rats injected with gold thiomalate, electron-dense deposits were observed in the lysosomes of glomerular epithelial cells indicating passage through the capillary wall. The formation of these deposits appeared to be dependent on the sulfur-containing portion of the gold thiomalate molecule since similar, though not identical, deposits were seen in animals injected with sodium thiomalate. In 2 patients with gold nephrotoxicity, the kidney showed deposits in the peripheral capillary wall of the glomerulus res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

1970
1970
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Our studies showed that in patients who have received chrysotherapy at some time during the course of rheumatoid disease Au becomes located within 'fixed' macrophages throughout the organs and tissues of the body. Some Au is also retained in significant amounts in the proximal tubular epithelium of the kidney; this observation is probably related to the passage of Au bound to serum protein, through the glomerulus and its subsequent reabsorption in the proximal tubular epithelium (Strunk and Ziff, 1970;Silverberg and others, 1970;Ganote, Beaver, and Moses, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies showed that in patients who have received chrysotherapy at some time during the course of rheumatoid disease Au becomes located within 'fixed' macrophages throughout the organs and tissues of the body. Some Au is also retained in significant amounts in the proximal tubular epithelium of the kidney; this observation is probably related to the passage of Au bound to serum protein, through the glomerulus and its subsequent reabsorption in the proximal tubular epithelium (Strunk and Ziff, 1970;Silverberg and others, 1970;Ganote, Beaver, and Moses, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…This could create prerequisite conditions for the formation of irritating concentrations of gold salts in the renal tissue. The fact remains that in the morphological picture of renal damage in the course of chrysotherapy, tubular damage is not in the fore and membranous glomerulonephritis predominates (4,6,9). On the other hand, a dominant feature of acute renal damage by salts of heavy metals is tubular necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a dominant feature of acute renal damage by salts of heavy metals is tubular necrosis. Light microscopic examination of the kidneys during treatment with gold salts revealed 'gold inclusions' in the tubular cells (6). The estimation of lactate dehydrogenase and both peptidases is an indicator of tubular cell damage, although these enzymes can be also indicators of non-renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several months after the last injection, the gold-containing inclusions had disappeared and kidney structure was normal. Some doubt has existed as to whether the dark granules within the lysosomes are actually gold, since somewhat similar granules can be seen in lysosomes of animals treated with sodium thiomalate without gold (12,26). However, Stuve et a2 (25) were able to confirm, by electronprobe microanalysis,, that these granules were indeed gold .+ Correlation of gold nephropathy with gold therapy.…”
Section: Discussionmentioning
confidence: 99%